Arabidopsis EDT1/HDG11 improves drought and salt tolerance in cotton and poplar and increases cotton yield in the field. Issue 1 (16th April 2015) - Yu, Lin‐Hui; Wu, Shen‐Jie; Peng, Yi‐Shu; Liu, Rui‐Na; Chen, Xi; Zhao, Ping; Xu, Ping; Zhu, Jian‐Bo; Jiao, Gai‐Li; Pei, Yan; Xiang, Cheng‐Bin
Summary: Drought and salinity are two major environmental factors limiting crop production worldwide. Improvement of drought and salt tolerance of crops with transgenic approach is an effective strategy to meet the demand of the ever‐growing world population. Arabidopsis ENHANCED DROUGHT TOLERANCE1/HOMEODOMAIN GLABROUS11 ( AtEDT1/HDG11 ), a homeodomain‐START transcription factor, has been demonstrated to significantly improve drought tolerance in Arabidopsis, tobacco, tall fescue and rice. Here we report that AtHDG11 also confers drought and salt tolerance in upland cotton ( Gossypium hirsutum ) and woody plant poplar ( Populus tomentosa Carr.). Our results showed that both the transgenic cotton and poplar exhibited significantly enhanced tolerance to drought and salt stress with well‐developed root system. In the leaves of the transgenic cotton plants, proline content, soluble sugar content and activities of reactive oxygen species‐scavenging enzymes were significantly increased after drought and salt stress compared with wild type. Leaf stomatal density was significantly reduced, whereas stomatal and leaf epidermal cell size were significantly increased in both the transgenic cotton and poplar plants. More importantly, the transgenic cotton showed significantly improved drought tolerance and better agronomic performance with higher cotton yield in the field both under normal and drought conditions. These results demonstrate that AtHDG11 is not only a promising candidate for crops improvement but also for woody plants.